2022
DOI: 10.1021/acs.jctc.1c01089
|View full text |Cite
|
Sign up to set email alerts
|

Energy Landscape of State-Specific Electronic Structure Theory

Abstract: State-specific approximations can provide a more accurate representation of challenging electronic excitations by enabling relaxation of the electron density. While state-specific wave functions are known to be local minima or saddle points of the approximate energy, the global structure of the exact electronic energy remains largely unexplored. In this contribution, a geometric perspective on the exact electronic energy landscape is introduced. On the exact energy landscape, ground and excited states form sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
39
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 127 publications
1
39
0
Order By: Relevance
“…To understand how these advantages come about, let us turn to discussing recent progress in the use of quasi-Newton methods to minimize energy-gradient-based objective functions, which have proven effective in the context of both the excited-state mean field (ESMF) ansatz and Kohn–Sham ΔSCF . Essentially, the idea is to search for energy saddle pointswhich in full CI (FCI) would be the exact excited statesby minimizing the norm of the energy gradient with respect to the variational parameters.…”
Section: Introductionmentioning
confidence: 99%
“…To understand how these advantages come about, let us turn to discussing recent progress in the use of quasi-Newton methods to minimize energy-gradient-based objective functions, which have proven effective in the context of both the excited-state mean field (ESMF) ansatz and Kohn–Sham ΔSCF . Essentially, the idea is to search for energy saddle pointswhich in full CI (FCI) would be the exact excited statesby minimizing the norm of the energy gradient with respect to the variational parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Symmetry breaking is expected to be similarly important in calculations of excited states. Excited states can be found as higher-energy self-consistent field (SCF) solutions of the KS equations, corresponding to stationary points on the electronic energy surface other than the ground state minimum. , Unlike TDDFT, such calculations are variational (i.e., based on the calculus of variation), and they can provide better approximations to long-range charge-transfer, ,, Rydberg, , core-level, , and other excitations , characterized by significant change in the electron density. However, while excited state DFT has been applied in a variety of fields, only a few studies of electronic near-degeneracies have been reported, ,, and the results appear to be contradictory.…”
mentioning
confidence: 99%
“…Excited states can be found as higher-energy self-consistent field (SCF) solutions of the KS equations, corresponding to stationary points on the electronic energy surface other than the ground state minimum. 26,[55][56][57][58][59][60][61][62][63][64][65] Unlike TDDFT, such calculations are variational (i. e. based on the calculus of variation), and can provide better approximations to long-range charge-transfer, 26,59,66 Rydberg, 67,68 core-level, 69,70 and other excitations 59,61 characterized by significant change in the electron density. However, while excited state DFT has been applied in a variety of fields, [71][72][73][74][75][76][77] only a few studies of electronic near-degeneracies have been reported 26,78,79 and the results appear contradictory.…”
mentioning
confidence: 99%